The impact of context on community interpreting research, practice & training - de Boe, Esther; Balogh, Katalin; Salaets, Heidi (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Although the notion of context is omnipresent in research in interpreting studies (IS), especially in community settings, and defines the ways in which interpreting is being practised, researched and trained, it has not yet been recognized or defined as a topic in its own right, at least not within IS. Starting from some theoretical notions on the concept of context, this article moves on to discuss different levels of context, namely, geographical, socio-institutional and interactional. By means of examples from a variety of settings in community interpreting (CI), it shows how the different levels of context interact, and, in these ways, have an impact on CI practice, research and training.